1998
DOI: 10.1093/toxsci/46.2.266
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Toxicity/Oncogenicity Study of Styrene in CD Rats by Inhalation Exposure for 104 Weeks

Abstract: Groups of 70 male and 70 female Charles River CD (Sprague-Dawley-derived) rats were exposed whole body to styrene vapor at 0, 50, 200, 500, or 1000 ppm 6 h/day 5 days/week for 104 weeks. The rats were observed daily, body weights and food and water consumption were measured periodically, and a battery of hematologic and clinical pathology examinations was conducted at weeks 13, 26, 52, 78, and 104. Nine or 10 rats per sex per group were necropsied after 52 weeks of exposure and the remaining survivors were nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(36 citation statements)
references
References 0 publications
7
28
1
Order By: Relevance
“…However, when exposed to cumene vapor, a higher incidence of alveolar/bronchiolar adenoma and carcinoma was observed in the lungs of mice of both sexes but not in rats (National Toxicology Program, 2009). Similar results were found for coumarin (National Toxicology Program, 1993), naphthalene (National Toxicology Program, 1992Program, , 2000, styrene (Cruzan et al, 1998(Cruzan et al, , 2001, ethylbenzene (National Toxicology Program, 1999), ␣-methylstyrene (AMS) (National Toxicology Program, 2007a), divinylbenzene (Na-tional Toxicology Program, 2007b), and benzofuran (National Toxicology Program, 1989), which are all structurally related. In contrast, a higher incidence of adenoma and carcinoma was observed in the kidney and not in the lung of male rats (and not female rats) versus controls in the 2-year toxicology and carcinogenesis studies conducted by the National Toxicology Program (2009).…”
Section: Introductionsupporting
confidence: 56%
“…However, when exposed to cumene vapor, a higher incidence of alveolar/bronchiolar adenoma and carcinoma was observed in the lungs of mice of both sexes but not in rats (National Toxicology Program, 2009). Similar results were found for coumarin (National Toxicology Program, 1993), naphthalene (National Toxicology Program, 1992Program, , 2000, styrene (Cruzan et al, 1998(Cruzan et al, , 2001, ethylbenzene (National Toxicology Program, 1999), ␣-methylstyrene (AMS) (National Toxicology Program, 2007a), divinylbenzene (Na-tional Toxicology Program, 2007b), and benzofuran (National Toxicology Program, 1989), which are all structurally related. In contrast, a higher incidence of adenoma and carcinoma was observed in the kidney and not in the lung of male rats (and not female rats) versus controls in the 2-year toxicology and carcinogenesis studies conducted by the National Toxicology Program (2009).…”
Section: Introductionsupporting
confidence: 56%
“…The purpose of our studies was to characterize the possible hepatotoxicity and pneumotoxicity associated with 4-vinylphenol in mice by making clinical pathology measurements and using histopathology. These endpoints and this species were selected because the lung and liver are known targets of styrene toxicity in mice (8,9,10,11,13,15,16) whereas in rats the pneumotoxicity is not observed (10,13). Male mice were used because they are more susceptible to the hepatotoxicity of styrene than are female mice (16) and were used in our previous studies on 4-vinylphenol metabolism (7) and styrene toxicity (11 Study Design: Because of the paucity of data regarding the toxicity of 4-VP, initial range nding studies were carried out in groups of 4 mice administered either 200 or 400 mg/kg 4-VP.…”
Section: Introductionmentioning
confidence: 99%
“…In the most informative cancer study, conducted by Cruzan et al (2001), an increase in pulmonary hyperplasia was observed in mice after 12 months of styrene inhalation exposure and incidence of lung tumors increased by the end of the study. In a rat study by Cruzan et al (1998), pulmonary hyperplasia was not increased, and the rats did not develop increased numbers of tumors. Harvard (Cohen et al, 2002) and IARC (2002) reviewed a study demonstrating an increase in pulmonary markers of toxicity (e.g., g-glutamyltranspeptidase and lactate dehydrogenase) after i.p.…”
Section: Genetic Toxicitymentioning
confidence: 89%
“…In a styrene inhalation study comparing male mice and rats, metabolic capacity was limited at concentrations Z300 ppm and was saturated at concentrations of B700 ppm in rats and 800 ppm in mice. In a study by Cruzan et al (1998), one section stated that blood levels of styrene and styrene oxide were proportional to dose in rats inhaling 50-1000 ppm styrene; another section of the report stated that some degree of saturation was noted between 200-1000 ppm styrene. A study in mice reported that blood styrene and styrene oxide levels were proportional to dose at styrene vapor concentrations of 20-160 ppm (Cruzan et al, 2001).…”
Section: Experimental Animalmentioning
confidence: 99%